A method for detecting baicalin and diclofenac sodium using an electrochemical sensor based on Cu-TCPP / BN composite material

Through electrochemical sensors modified based on Cu-TCPP/BN composite materials, the problem of difficulty in detecting diclofenac sodium and baicalin in the prior art is solved, and efficient and stable detection results are achieved.

CN116106381BActive Publication Date: 2025-04-11GUANGXI NORMAL UNIV FOR NATITIES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211730007.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-30
Publication Date
2025-04-11
Estimated Expiration
2042-12-30

AI Technical Summary

Technical Problem

The existing methods are difficult to detect diclofenac sodium and baicalin simultaneously quickly and efficiently, and there are problems such as time-consuming, high cost or complex operation.

Method used

The electrochemical sensor modified based on Cu-TCPP/BN composite material was used to detect baicalin and diclofenac sodium by differential pulse voltammetry, which improved the conductivity and sensitivity of the electrode.

Benefits of technology

It realizes rapid and simple quantitative detection of baicalin and diclofenac sodium, with low detection limit, high stability, good reproducibility and anti-interference ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004031238410000101
    Figure BDA0004031238410000101
  • Figure BDA0004031238410000111
    Figure BDA0004031238410000111
  • Figure HDA0004031238420000011
    Figure HDA0004031238420000011
Patent Text Reader

Abstract

The present invention relates to the field of electrochemical analysis technology, and specifically discloses a method for simultaneously detecting baicalin and diclofenac sodium by an electrochemical sensor based on a Cu-TCPP / BN composite material, including: synthesizing a Cu-TCPP / BN composite material; the Cu-TCPP / BN composite material is dispersed in a solvent to obtain a Cu-TCPP / BN dispersion, which is drop-coated on the surface of a glassy carbon electrode, dried, and a Cu-TCPP / BN modified electrode is obtained; the Cu-TCPP / BN modified electrode is used as a working electrode, and a three-electrode system is formed with an auxiliary electrode and a reference electrode, and an electrochemical workstation is used to construct an electrochemical sensor. The method for simultaneously detecting baicalin and diclofenac sodium by an electrochemical sensor based on a Cu-TCPP / BN composite material of the present invention can quickly and easily perform quantitative detection of baicalin and diclofenac sodium at the same time. The electrochemical sensor based on a Cu-TCPP / BN composite material of the present invention has a low detection limit, high stability, good reproducibility and anti-interference ability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemical analysis, and particularly relates to a method for detecting baicalin and diclofenac sodium by an electrochemical sensor based on a Cu-TCPP / BN composite material. Background Art

[0002] Diclofenac sodium (DS) is a non-steroidal anti-inflammatory drug with anti-inflammatory, analgesic and antipyretic effects. It is mainly used for postoperative pain, tuberculosis, arthritis, etc. It is a white or white-like powder with a pungent smell and is easily soluble in alcohol. Baicalin is a flavonoid compound extracted from the dried rhizome of the dicotyledonous plant Scutellaria baicalensis, which has anti-inflammatory, anti-allergic, antibacterial, antiviral, and anti-malignant tumor effects. Scutellaria baicalensis is a commonly used Chinese medicine preparation, in which baicalin is a commonly used marker. At present, it has been publicly used to combine diclofenac sodium non-steroidal anti-inflammatory drugs and baicalin for animal antipyretic and analgesic, which has obvious synergistic effects and can effectively reduce adverse drug reactions. At present, the methods for publicly determining diclofenac sodium or baicalin mainly include high-performance liquid chromatography, ultraviolet spectrophotometry, and liquid-mass spectrometry, etc. These methods have the advantages of sensitivity and accuracy, but have the disadvantages of being time-consuming, high cost or complicated operation. Therefore, it is of great significance to establish a rapid, efficient method for simultaneous detection of diclofenac sodium and baicalin.

[0003] Electrochemical sensors refer to sensors that convert chemical information into electrical signals according to certain rules based on the electrochemical properties of the object being measured, and then use the reaction signals to perform qualitative and quantitative analysis on the object. Three different electrode structures are generally used to ensure that the glassy carbon electrode can maintain a stable potential during use. It plays an important role in drug analysis, environmental monitoring, food classification, and medical testing. This is a very effective method to detect traces of one or more targets. At present, there are no publicly reported electrochemical sensors that can simultaneously detect diclofenac sodium and baicalin. Summary of the invention

[0004] The purpose of the present invention is to provide a method for detecting baicalin and diclofenac sodium by an electrochemical sensor based on a Cu-TCPP / BN composite material, and the simultaneous testing of baicalin and diclofenac sodium also has good stability, reproducibility and anti-interference.

[0005] To achieve the above object, the present invention provides a method for detecting baicalin and diclofenac sodium using an electrochemical sensor based on a Cu-TCPP / BN composite material, comprising establishing an electrochemical sensor based on a Cu-TCPP / BN composite material, wherein the establishment of the electrochemical sensor based on the Cu-TCPP / BN composite material comprises the following steps:

[0006] (1) Cu(NO3)2, PVP and trifluoroacetic acid are sequentially added to a DMF-ethanol mixture to obtain a mixed solution A; TCPP is added to another DMF-ethanol mixture to obtain a mixed solution B, the mixed solution B is added dropwise to the mixed solution A to mix well, BN is added for ultrasonic dispersion, and then refluxed at 70-90°C for 15-20h, cooled, centrifuged, washed, and vacuum dried to obtain a Cu-TCPP / BN composite material;

[0007] (2) The Cu-TCPP / BN composite material is dispersed in a solvent to obtain a Cu-TCPP / BN dispersion, which is drop-coated on the surface of a glassy carbon electrode and dried to obtain a Cu-TCPP / BN modified electrode;

[0008] (3) The Cu-TCPP / BN modified electrode obtained in step (2) is used as a working electrode to form a three-electrode system with an auxiliary electrode and a reference electrode, and is used in conjunction with an electrochemical workstation to construct an electrochemical sensor.

[0009] Preferably, in the above method for detecting baicalin and diclofenac sodium, in step (1), the DMF-ethanol mixed solution is obtained by mixing DMF and ethanol in a volume ratio of 3:1.

[0010] Preferably, in the above method for detecting baicalin and diclofenac sodium, in the step (1), the ratio of Cu(NO3)2, PVP, trifluoroacetic acid and DMF-ethanol mixed solution in the mixed solution A is 3-4 mg:8.5-11 mg:9-12 μL:10-13 mL, and the trifluoroacetic acid is a trifluoroacetic acid solution diluted with anhydrous ethanol to a 1 mol / L solution.

[0011] Preferably, in the above method for detecting baicalin and diclofenac sodium, in step (1), the ratio of TCPP to DMF-ethanol mixed solution in the mixed solution B is 1 mg: 0.8-1.2 mL, and the amount of BN added is 30-33 times the amount of TCPP used.

[0012] Preferably, in the above method for detecting baicalin and diclofenac sodium, in step (2), the concentration of the Cu-TCPP / BN dispersion is 0.8-1.2 mg / mL, and the solvent is anhydrous ethanol.

[0013] Preferably, in the above method for detecting baicalin and diclofenac sodium, the glassy carbon electrode is pretreated before use, and the pretreatment is: polishing the glassy carbon electrode with a solution prepared with aluminum oxide, and the electrode can be cleaned with deionized water only when the potential difference is less than 75mV twice, and then naturally dried.

[0014] Preferably, the above method for detecting baicalin and diclofenac sodium further comprises the following steps:

[0015] S1. adding baicalin and diclofenac sodium standard solutions to an electrolyte to prepare a series of mixed standard solutions of different concentrations; immersing the three-electrode system in the mixed standard solution for differential pulse voltammetry detection, using the concentrations of baicalin and diclofenac sodium in the mixed standard solution as the abscissa and the corresponding peak current as the ordinate to establish standard curves of baicalin and diclofenac sodium, respectively;

[0016] S2. Take the sample to be tested and add it to the electrolyte to obtain a mixed solution to be tested, place three electrodes in the mixed solution to be tested for reaction, perform differential pulse voltammetry scanning, record the peak current, and combine with the standard curve to obtain the content of baicalin and diclofenac sodium in the sample to be tested.

[0017] Preferably, in the above method for detecting baicalin and diclofenac sodium, in step S1, the electrolyte is a PBS buffer solution, the concentration of the PBS buffer solution is 0.1 mol / L, and the pH is 7.

[0018] Preferably, in the above method for detecting baicalin and diclofenac sodium, differential pulse voltammetry is used for detection, with a potential range of -0.2 to 1.0 V and a scan rate of 0.1 V / s.

[0019] Compared with the existing technology, the present invention has the following beneficial effects:

[0020] In the method for detecting baicalin and diclofenac sodium by using an electrochemical sensor based on a Cu-TCPP / BN composite material of the present invention, a copper porphyrin-BN composite material is used to modify an electrode to improve the conductivity and sensitivity of the electrode, and its conductivity is significantly better than that of a copper porphyrin or BN single material modification, and the copper porphyrin and BN composite modified electrodes have a synergistic effect. Constructing an electrochemical sensor based on a Cu-TCPP / BN composite material can quickly and easily perform quantitative detection of baicalin and diclofenac sodium at the same time. The electrochemical sensor based on a Cu-TCPP / BN composite material of the present invention has a low detection limit, high stability, good reproducibility and anti-interference ability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The scanning electron microscope images of different materials in the embodiments of the present invention and the comparative examples are as follows: (a) BN; (b) TCPP; (c) Cu-TCPP; (d) Cu-TCPP@BN.

[0022] Figure 2 The XRD patterns of different materials in the embodiments and comparative examples of the present invention are shown in FIG.

[0023] Figure 3 The electrochemical impedance spectra of electrodes modified with different materials in Example 1 and Comparative Examples 1 to 3 of the present invention are shown.

[0024] Figure 4 The cyclic voltammetry curves of electrodes modified with different materials in Example 1 of the present invention and Comparative Examples 1 to 3 are shown.

[0025] Figure 5 (A) SWV diagram of the electrochemical response of baicalin and diclofenac sodium at different pH values; (B) The effect of pH on the peak current change; (B) The relationship between peak potential and pH.

[0026] Figure 6 (A) Cyclic voltammetry curves of baicalin at different scanning rates; (B) Relationship between peak current and scanning rate; (C) Relationship between natural logarithm of scanning rate and potential; (D) Cyclic voltammetry curves of diclofenac sodium at different scanning rates; (E) Relationship between potential and logarithm of scanning rate; (F) Relationship between square root of scanning rate and current.

[0027] Figure 7 (A) is the DPV graph of measuring different concentrations of baicalin at a fixed concentration of diclofenac sodium in Example 2; (B) is the linear relationship graph between peak current and baicalin concentration.

[0028] Figure 8 (C) is the DPV graph and peak current of different concentrations of diclofenac sodium tested at a fixed baicalin concentration in Example 2; (D) is the linear relationship graph of diclofenac sodium concentration.

[0029] Fig. 9 (E) is a DPV diagram of a mixed solution of baicalin and diclofenac sodium with different concentrations tested simultaneously in Example 2; (F) is a linear relationship diagram between the peak current and concentration of baicalin; (G) is a linear relationship diagram between the peak current and concentration of diclofenac sodium. DETAILED DESCRIPTION

[0030] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0031] Example 1

[0032] This embodiment provides a method for preparing an electrochemical sensor based on a Cu-TCPP / BN composite material, comprising the following steps:

[0033] (1) Synthesis of Cu-TCPP / BN composite material: Prepare a mixed solution of N,N-dimethylformamide (DMF)-ethanol (volume ratio 3:1), add 7.2 mg of Cu(NO3)2 and 20.0 mg of polyvinylpyrrolidine copper K30 (PVP) to 24.0 mL of DMF-ethanol mixed solution, and then add 20 μL of trifluoroacetic acid diluted to 1 mol / L with anhydrous ethanol to obtain a mixed solution A;

[0034] 8.0 mg of porphyrin (TCPP) was added to another 8.0 mL of DMF-ethanol mixed solution, and the mixture was evenly mixed to obtain a mixed solution B. Under the action of magnetic stirring, the mixed solution B was slowly dripped into the mixed solution A with a rubber-tipped dropper, and 250.0 mg of boron nitride (BN) was added, and ultrasonication was performed for 10 minutes to achieve diffusion equilibrium.

[0035] Finally, the mixture was transferred to a 100 mL three-necked round-bottom flask, a reflux device was set up, and the mixture was heated to 80°C in a water bath under stirring with a magnetic stirrer, and refluxed at a constant temperature for 18 hours. The mixture was naturally cooled to room temperature to obtain a sediment, which was first washed with deionized water, transferred to a centrifuge tube and centrifuged for 8 minutes, and the washing and centrifugation were repeated five times. The sediment was then washed with anhydrous ethanol solvent and centrifuged for 8 minutes. The process was repeated five times, and the washed sediment was then placed in a vacuum drying oven and dried at 50°C for 6 hours to obtain a Cu-TCPP / BN composite material.

[0036] (2) Preparation of Cu-TCPP / BN modified electrode (Cu-TCP@BN / GCE):

[0037] Before modifying the glassy carbon electrode, the glassy carbon electrode was polished with a solution prepared with aluminum oxide. The electrode could be cleaned with deionized water only when the potential difference was less than 75 mV twice, and then naturally dried. 1.0 mg of Cu-TCPP / BN composite material was weighed and put into a centrifuge tube. 1.0 mL of anhydrous ethanol was added to the centrifuge tube. The composite material was fully dispersed in the anhydrous ethanol by ultrasonication for 10 min to obtain a Cu-TCPP / BN dispersion. 10 μL of the ultrasonicated Cu-TCPP / BN dispersion was measured with a pipette and dropped into the middle of the treated glassy carbon electrode. The glass cover was covered and the glassy carbon electrode was placed next to an infrared lamp to dry to obtain a Cu-TCPP / BN modified electrode.

[0038] (3) The Cu-TCPP / BN modified electrode obtained in step (2) is used as a working electrode, a calomel electrode is used as a reference electrode, and a platinum wire electrode is used as an auxiliary electrode to form a three-electrode system, which is then connected to an electrochemical workstation to construct an electrochemical sensor.

[0039] Comparative Example 1Cu-TCPP modified electrode (Cu-TCPP / GCE)

[0040] Cu-TCPP material synthesis: Prepare a mixed solution of N,N-dimethylformamide (DMF)-ethanol (volume ratio 3:1), add 7.2 mg Cu(NO3)2 and 20.0 mg polyvinylpyrrolidine copper K30 (PVP) to 24.0 mL DMF-ethanol mixed solution, and then add 20 μL of trifluoroacetic acid diluted to 1 mol / L with anhydrous ethanol to obtain a mixed solution A;

[0041] 8.0 mg of porphyrin (TCPP) was added to another 8.0 mL of DMF-ethanol mixed solution, and the mixture was uniformly mixed to obtain a mixed solution B; under the action of magnetic stirring, the mixed solution B was slowly added dropwise to the mixed solution A with a rubber-tipped dropper, and the mixture was uniformly mixed, and ultrasonicated for 10 minutes, and then a hydrothermal method was used: hydrothermal reaction was carried out at 80° C. for 18 hours; it was naturally cooled to room temperature, and the obtained precipitate was washed with deionized water, centrifuged and repeated 5 times, and washed with ethanol, centrifuged and repeated 5 times, and then placed in an electric heating blast drying oven, and dried at 50° C. for 6 hours to obtain a Cu-TCPP material;

[0042] Before modifying the glassy carbon electrode, polish the glassy carbon electrode with a solution prepared with aluminum oxide. The electrode can be cleaned with deionized water only when the potential difference is less than 75 mV twice, and then dried naturally. 1.0 mg of Cu-TCPP material is weighed and placed in a centrifuge tube. 1.0 mL of anhydrous ethanol is added to the centrifuge tube. Ultrasonication is performed for 10 minutes to fully disperse the composite material in the anhydrous ethanol to obtain a Cu-TCPP dispersion. 10 μL of the ultrasonicated Cu-TCPP dispersion is measured with a pipette and dropped into the middle of the treated glassy carbon electrode. The glass cover is covered and the glassy carbon electrode is placed next to an infrared lamp to dry to obtain a Cu-TCPP modified electrode.

[0043] Comparative Example 2 TCPP modified electrode (TCPP / GCE)

[0044] The steps for preparing the TCPP modified electrode are the same as step (2) in Example 1, except that TCPP is used to replace the Cu-TCPP / BN composite material.

[0045] Comparative Example 3 BN modified electrode (BN / GCE)

[0046] The preparation steps of the BN modified electrode are the same as step (2) in Example 1, except that BN is used to replace the Cu-TCPP / BN composite material.

[0047] Material characterization: SEM images of BN, TCPP, Cu-TCPP, and Cu-TCPP / BN composites are shown in Figure 1 As can be seen from the figure, BN is a micro-nano particle, TCPP is a strip-shaped structure, and Cu-TCPP is a sheet-like structure with irregular stacking. The surface of the Cu-TCPP / BN composite material has both the sheet-like morphology of Cu-TCPP and the morphology of BN nanosheets, indicating that Cu-TCPP and BN nanosheets are successfully composited. Figure 2The XRD patterns of BN, TCPP, Cu-TCPP, and Cu-TCPP / BN composite materials show that Cu-TCPP has peaks at 29° and 43°. BN has peaks at 28°, 42°, 53°, and 76°, and the peak shape gradually weakens. The peak of Cu-TCPP / BN is sharper than that of BN, and its peak shape is very similar to that of BN, which indirectly indicates that Cu-TCPP and BN are successfully composited.

[0048] (I) Characterization of different modified electrodes:

[0049] Electron transfer resistance is used to indicate the electron transfer ability of an electrode. Electron transfer resistance is proportional to electron transfer resistance. Electrochemical impedance spectroscopy (EIS) was used to measure the electron transfer between electrodes modified with different materials. Electrodes modified with different materials were subjected to 5.0 mmol / L [Fe(CN)6] 3- / 4- The electrochemical impedance spectrum of the solution as an electrolyte is as follows Figure 3 As shown, from Figure 3 It can be seen that TCPP and Cu 2+ The resistance of Cu-TCPP obtained after compounding is smaller than that of TCPP, thereby accelerating the rate of electron transfer. BN has better electrical properties. The resistance of Cu-TCPP / BN composite material obtained by compounding Cu-TCPP and BN is smaller than that of BN and Cu-TCPP, and the electron transfer rate is greater than that of BN and Cu-TCPP. After Cu-TCPP / BN is compounded, the electrochemical resistance is reduced and the electron transfer rate is accelerated. The two have a synergistic effect.

[0050] In the presence of 1.00×10 -5 mol / L baicalin and 1.00×10 -5 Cyclic voltammetry studies were performed on different modified electrodes in PBS buffer solutions of 0.1 mol / L diclofenac sodium pH 7.0 and 0.1 mol / L, with a scan rate of 0.1 V / s and a potential range of -0.2 to 1 V. The results are shown in Figure 4 .Depend on Figure 4 It can be seen that Bare / GCE, BN / GCE, TCPP / GCE, Cu-TCPP / GCE, and Cu-TCPP@BN / GCE all have obvious oxidation peaks at 0.2 V and 0.6 V, corresponding to the oxidation of baicalin and diclofenac sodium, respectively. As can be seen from the figure, the oxidation peak currents of baicalin and diclofenac sodium of Bare / GCE are 3.79×10 -7 A and 7.40×10 -7 A, the peak currents of baicalin and diclofenac sodium oxidation of Cu-TCP@BN / GCE were 1.72×10 -6 A and 1.48×10 -6A is about 4.5 times and 2.0 times of the oxidation peak current of baicalin and diclofenac sodium of Bare / GCE. It can be seen that the Cu-TCPP@BN composite material has a significant response to the oxidation peak current of baicalin and diclofenac sodium, which promotes the electrochemical oxidation reaction of baicalin and diclofenac sodium on the electrode and increases the electrochemical response.

[0051] (II) Optimization of detection conditions

[0052] (1) Electrolyte

[0053] In the presence of 1.50×10 -5 mol / L baicalin and 1.50×10 -5 The influence of different pH values ​​was studied in a PBS buffer solution of 50 mol / L diclofenac sodium. The three-electrode system of Example 1 was used to perform experimental analysis and research in the pH range of 3.0 to 9.0 by square wave voltammetry (SWV). The results are shown in Table 1. Figure 5 .Depend on Figure 5 (B) It can be seen that in the buffer solution pH range of 3.0 to 6.0, the oxidation peak current of diclofenac sodium increases with the increase of solution pH value. At this time, the maximum value of the peak current is 9.63×10 -7 A, when the pH value is 6.0-9.0, the oxidation peak current will also decrease with the increase of pH value; when the pH value of the buffer solution is 3.0-8.0, the oxidation peak current of baicalin will also increase with the increase of pH value, and the highest value of the peak current is 9.96×10 -7 A, pH 8.0-9.0 The oxidation peak current will decrease as the pH increases; Figure 5 (A) It can be seen that at pH 7, the peak shapes of baicalin and diclofenac sodium are the best, the oxidation peaks of the two substances are far apart, they have no effect on each other, and their oxidation responses are also relatively good. Based on the above structure, the PBS buffer solution with a pH of 7.0 is the optimal electrolyte.

[0054] from Figure 5 C shows that there is a good linear relationship between the pH value and peak potential of the buffer solution. The linear relationship between the pH value and the peak potential of baicalin is as follows: Epa = -0.0714pH + 0.6795, R 2 =0.9912; the linear relationship of diclofenac sodium is: Epa = -0.515pH + 0.9436, R 2=0.9921. The absolute value of the slope of the linear equation of baicalin is 71.40 mV, which is close to the theoretical value (59.20 mV), indicating that the number of electron transfers in the electrochemical reaction of baicalin is equal to the number of transferred protons. Similarly, the absolute value of the slope of the linear equation of diclofenac sodium is 51.50 mV, which is close to the theoretical value (59.20 mV), indicating that the number of electron transfers in the electrochemical reaction of diclofenac sodium is equal to the number of transferred protons.

[0055] (2) Scan rate

[0056] Using the three-electrode system of Example 1, cyclic voltammetry (CV) was performed in a solution containing 1.50×10 -5 The cyclic voltammetry curve of baicalin was tested on Cu-TCPP@BN / GCE with a 10 mol / L baicalin solution and a pH 7.0 PBS buffer solution. Figure 6 As shown in (A) and (B), under the same experimental conditions and scanning rates of 0.01 to 1 V / s, the oxidation peak current of baicalin increases with the increase of the scanning rate, and a linear relationship between the scanning rate and the peak current can be obtained: Ipa (μA) = 1.00 × 10 -6 v+3.00×10 -7 (V ·s -1 , R 2 =0.9927). Figure 6 (C) It can also be obtained that the linear relationship between the potential (Ep) and the logarithm of the scanning rate (lnv) is: Epa = 0.0098lnv (V / s) + 0.1867, R 2 =0.9936. This indicates that the redox process of baicalin on Cu-TCPP@BN / GCE is an adsorption-controlled process.

[0057] Under the same experimental conditions, at a concentration of 1.50×10 -5 The cyclic voltammetry curve of diclofenac sodium in Cu-TCPP@BN / GCE was studied in the presence of 1 mol / L diclofenac sodium solution and pH 7.0 PBS buffer solution. Figure 6 As shown in (D) and (E), under the same experimental conditions and scanning rates of 0.01 to 0.1 V / s, the oxidation peak current of diclofenac sodium increases with the increase of the scanning rate. The linear relationship between the square root of the scanning rate and the peak current can be obtained: Ipa (μA) = 4.00 × 10 - 7 v 1 / 2 +2.00×10 -7 (R 2 =0.9956), the linear relationship between potential (Ep) and scan rate logarithm (lnv): Epa = 0.03lnv (V / s) + 0.737 (R 2=0.9909). The linear relationship between the peak current and the square root of the scan rate shows that the electrochemical oxidation process of diclofenac sodium on Cu-TCPP@BN / GCE is a surface diffusion-controlled process.

[0058] Example 2

[0059] A method for simultaneously detecting baicalin and diclofenac sodium using an electrochemical sensor based on a Cu-TCPP / BN composite material comprises the following steps:

[0060] S1. The Cu-TCPP / BN modified electrode prepared in Example 1 was used as the working electrode, the platinum wire was used as the auxiliary electrode, and the calomel electrode was used as the reference electrode to form a three-electrode system:

[0061] S2. Add baicalin and diclofenac sodium standard solutions to the electrolyte to prepare a series of mixed standard solutions of different concentrations; immerse the three-electrode system of step S1 in the mixed solution for differential pulse voltammetry (DPV) detection, and establish a standard curve of baicalin and diclofenac sodium with the concentration of baicalin and diclofenac sodium in the mixed standard solution as the abscissa and the corresponding peak current as the ordinate;

[0062] S3. Take the sample to be tested and add it to the electrolyte to obtain a mixed solution to be tested, place three electrodes in the mixed solution to be tested for reaction, perform differential pulse voltammetry scanning, record the peak current, and combine with the standard curve to obtain the content of baicalin and diclofenac sodium in the sample to be tested.

[0063] The concentration of diclofenac sodium was fixed at 3.00×10 -6 mol / L, differential pulse voltammetry (DPV) was used to study the effects of baicalin at different concentrations. Figure 7 .Depend on Figure 7 (A) It can be seen that with the increase of baicalin concentration, its oxidation peak current also gradually increases, and the concentration range is 1.00×10 -7 mol / L~5.00×10 -5 mol / L, the peak current of baicalin showed a good linear relationship with its concentration. Figure 7 (B), the linear equation is: I (μA) = 0.0046C (μmol / L) + 2.00 × 10 -8 (R 2 =0.9905), the detection limit is 4.52×10 -8 mol / L.

[0064] The fixed concentration of baicalin was 5.00×10 -6 mol / L, differential pulse voltammetry (DPV) was used to study the effects of different concentrations of diclofenac sodium. The results are shown in Figure 8 .Depend on Figure 8(C) and (D) show that with the increase of diclofenac sodium concentration, its oxidation peak current also gradually increases. -7 mol / L~1.90×10 -5 mol / L concentration range, the peak current and concentration show a good linear relationship, and the linear equation is: I (μA) = 0.0134C (μmol / L) + 3.00 × 10 -8 (R 2 =0.9902), the detection limit is 1.68×10 -8 mol / L.

[0065] Differential pulse voltammetry (DPV) was used to study the effects of different concentrations of baicalin and diclofenac sodium. Fig. 9 Baicalin and diclofenac sodium at 3.00×10 -7 mol / L~1.20×10 -5 In the concentration region of mol / L, the peak current shows a good linear relationship with the concentration. Fig. 9 (F), the linear equation of baicalin is as follows: I (μA) = 0.0262C (μmol / L) + 1.00 × 10 -8 (R 2 =0.9920), the detection limit is 1.15×10 -8 mol / L; see Fig. 9 (G), the linear equation of diclofenac sodium is as follows: I (μA) = 0.0146C (μmol / L) + 1.00 × 10 -8 (R 2 =0.9902), the detection limit is 6.44×10 -8 mol / L. When only diclofenac sodium or baicalin is contained, the above single linear equation is used as the standard for detection. For example, there is no baicalin in diclofenac sodium capsules, which exists in a single form, and a single linear equation is used; when two components of diclofenac sodium and baicalin are contained, the above bilinear equation is used as the standard for detection. For example, when the sample contains two drugs, such as blood, a bilinear equation is used.

[0066] 1. Stability and reproducibility

[0067] Under the optimal experimental conditions, differential pulse voltammetry (DPV) was used to detect the stability and reproducibility of Cu-TCPP@BN / GCE. -5In the PBS buffer solution of 1 mol / L baicalin and diclofenac sodium at pH = 7, the same Cu-TCPP@BN / GCE was used as the working electrode, and the detection was carried out 12 times continuously and the data was recorded. The relative standard deviations of the peak currents of baicalin and diclofenac sodium were calculated respectively. Their relative standard deviations were 2.43% and 3.61%, respectively. This shows that the Cu-TCPP@BN modified electrode has good stability. In addition, the five polished glassy carbon electrodes were modified with the Cu-TCPP / BN composite material at the same time. Under the same experimental conditions, their peak current values ​​were measured and the data were recorded. After calculation, their relative standard deviations were 3.19% and 4.35%, respectively, indicating that the reproducibility of the material is relatively good.

[0068] 2. Anti-interference

[0069] The anti-interference ability of Cu-TCPP / BN composite modified electrode to other drugs was studied under the optimal conditions. Differential pulse voltammetry (DPV) was used to test the -5 mol / L baicalin solution and 5.00×10 -5 mol / L diclofenac sodium solution in PBS buffer solution, record the peak current, then add a certain concentration of interfering substance solution, and then record the peak current after adding the interfering substance. The relative error of the two peak currents is shown in Table 1. The relative error is less than ±5%, and the effect of the interfering substance on the determination of baicalin and diclofenac sodium is negligible, which shows that Cu-TCPP@BN / GCE has good selectivity for baicalin and diclofenac sodium.

[0070] Table 1 Effects of different interfering substances on the electrochemical behavior of Cu-TCPP / BN modified electrode

[0071]

[0072]

[0073] 3. Recyclability

[0074] In order to investigate the detection ability of Cu-TCPP@BN / GCE for actual samples, the electrochemical sensor constructed by Cu-TCPP@BN / GCE was analyzed by differential pulse voltammetry (DPV) under the optimal experimental conditions. The average spike recovery rate of baicalin capsules was 101.82% and the relative standard deviation of peak current was 1.26%. The average spike recovery rate of diclofenac sodium sustained-release capsules was 98.45% and the relative standard deviation of peak current was 2.63%. The spike recovery rate and relative standard deviation of peak current of baicalin capsules and diclofenac sodium sustained-release capsules were small, so the Cu-TCPP / BN modified electrode can be used for the content determination of baicalin capsules and diclofenac sodium sustained-release capsules in actual samples. The baicalin capsules used in the experiment, 0.25g / pill, were from Dongguan Jinmeiji Pharmaceutical Co., Ltd.; diclofenac sodium sustained-release tablets, 50mg / pill, were from Yaoda Pharmaceutical Co., Ltd.

[0075] The standard solutions of baicalin and diclofenac sodium used in the above experiments were prepared as follows: 22.0 mg of baicalin was weighed using an analytical balance, dissolved in 50.0 mL of anhydrous ethanol, and ultrasonicated in an ultrasonic machine for 10 min to disperse it evenly, and a concentration of 1.00 × 10 -3 mol / L baicalin standard solution. Use an analytical balance to weigh 15.0 mg of diclofenac sodium, dissolve it in 50.0 mL of anhydrous ethanol, and then place it in an ultrasonic machine for 10 minutes to make it evenly dispersed. The concentration of 1.00×10 -3 Then, baicalin standard solution, diclofenac sodium standard solution and anhydrous ethanol were used to prepare baicalin and diclofenac sodium standard solutions of different concentrations.

[0076] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A method for detecting baicalin and diclofenac sodium using an electrochemical sensor based on a Cu-TCPP / BN composite material, characterized in that: The method comprises establishing an electrochemical sensor based on a Cu-TCPP / BN composite material, wherein the electrochemical sensor based on the Cu-TCPP / BN composite material comprises the following steps: (1) Cu(NO3)2, PVP and trifluoroacetic acid are sequentially added to a DMF-ethanol mixture to obtain a mixed solution A; TCPP is added to another DMF-ethanol mixture to obtain a mixed solution B, the mixed solution B is added dropwise to the mixed solution A to mix well, BN is added for ultrasonic dispersion, and then refluxed at 70-90°C for 15-20h, cooled, centrifuged, washed, and vacuum dried to obtain a Cu-TCPP / BN composite material; (2) The Cu-TCPP / BN composite material is dispersed in a solvent to obtain a Cu-TCPP / BN dispersion, which is drop-coated on the surface of a glassy carbon electrode and dried to obtain a Cu-TCPP / BN modified electrode; (3) The Cu-TCPP / BN modified electrode obtained in step (2) is used as a working electrode to form a three-electrode system with an auxiliary electrode and a reference electrode, and is connected to an electrochemical workstation to construct an electrochemical sensor.

2. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: In the step (1), the DMF-ethanol mixed solution is obtained by mixing DMF and ethanol in a volume ratio of 3:

1.

3. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: In the step (1), the ratio of Cu(NO3)2, PVP, trifluoroacetic acid and DMF-ethanol mixed solution in the mixed solution A is 3-4 mg:8.5-11 mg:9-12 μL:10-13 mL, and the trifluoroacetic acid is a trifluoroacetic acid solution diluted with anhydrous ethanol to a 1 mol / L solution.

4. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: In the step (1), the ratio of TCPP to DMF-ethanol mixed solution in the mixed solution B is 1 mg: 0.8-1.2 mL, and the amount of BN added is 30-33 times the amount of TCPP used.

5. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: In the step (2), the concentration of the Cu-TCPP / BN dispersion is 0.8-1.2 mg / mL, and the solvent is anhydrous ethanol.

6. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: The glassy carbon electrode is pretreated before use. The pretreatment includes polishing the glassy carbon electrode with a solution prepared with aluminum oxide. The electrode can be cleaned with deionized water only when the potential difference is less than 75 mV twice, and then dried naturally.

7. The method for detecting baicalin and diclofenac sodium according to claim 1, characterized in that: The following steps are also included: S1. adding baicalin and diclofenac sodium standard solutions to an electrolyte to prepare a series of mixed standard solutions of different concentrations; immersing the three-electrode system in the mixed standard solution for differential pulse voltammetry detection, using the concentrations of baicalin and diclofenac sodium in the mixed standard solution as the abscissa and the corresponding peak current as the ordinate to establish standard curves of baicalin and diclofenac sodium, respectively; S2. Take the sample to be tested and add it to the electrolyte to obtain a mixed solution to be tested, place three electrodes in the mixed solution to be tested for reaction, perform differential pulse voltammetry scanning, record the peak current, and combine with the standard curve to obtain the content of baicalin and diclofenac sodium in the sample to be tested.

8. The method for simultaneous detection of baicalin and diclofenac sodium according to claim 7, characterized in that: In step S1, the electrolyte is a PBS buffer solution, the concentration of the PBS buffer solution is 0.1 mol / L, and the pH is 7.

9. The method for detecting baicalin and diclofenac sodium according to claim 7, characterized in that: Differential pulse voltammetry was used for detection with a potential range of -0.2 to 1.0 V and a scan rate of 0.1 V / s.

Citation Information

Patent Citations

  • Electrochemical sensor for detecting glyphosate based on copper porphyrin metal organic framework modified carbon paper electrode

    CN114324515A

  • Electrochemical biosensor based on metal organic framework hybrid nanosheet and method for detecting lactic acid content in sweat by using electrochemical biosensor

    CN114487061A